Generation of high-field terahertz pulses in an HMQ-TMS organic crystal pumped by an ytterbium laser at 1030 nm - Rovere, Andrea; Jeong, Young Gyun; Piccoli, Riccardo; Lee, Seung Heon; Lee, Seung Chul; Kwon, O. Pil; Jazbinsek, Mojca; Morandotti, Roberto; Razzari, Luca (Optics Express, 2018)
We present the generation of high-peak-electric-field terahertz pulses via collinear optical rectification in a 2-(4-hydroxy-3-methoxystyryl)-1-methilquinolinium-2,4,6-trimethylbenzenesulfonate (HMQ-TMS) organic crystal. The crystal is pumped by an amplified ytterbium laser system, emitting 170-fs-long pulses centered at 1030 nm. A terahertz peak electric field greater than 200 kV/cm is obtained for 420 µJ of optical pump energy, with an energy conversion efficiency of 0.26% - about two orders of magnitude higher than in common inorganic crystals collinearly pumped by amplified femtosecond lasers. An open-aperture Z-scan measurement performed on an n-doped InGaAs thin film using such terahertz source shows a nonlinear increase in the terahertz transmission of about 2.2 times. Our findings demonstrate the potential of this terahertz generation scheme, based on ytterbium laser technology, as a simple and efficient alternative to the existing intense table-top terahertz sources. In particular, we show that it can be readily used to explore nonlinear effects at terahertz frequencies.
Keywords: Inorganic crystals; Optical rectifications; Orders of magnitude; Peak electric field; Terahertz frequencies; Terahertz generation; Terahertz transmission; Z-scan measurement